KAJIAN PENGARUH VARIASI KEMIRINGAN CHUTE TERHADAP KECEPATAN DAN JENIS ALIRAN DI SALURAN TERBUKA - Anggraheni, Dinia; Pratiwi, Dwi Astuti Wahyu Wulan; Tazka, Arief El Hakam; Haq, Ikbar Dlialul (Jurnal Teknik Sipil dan Arsitektur, 2025)
Studies related to flow in open channels are still very important to support understanding of flow behavior and also applications in civil engineering such as the construction of irrigation and drainage channels to increase efficiency and better design. Most of the designed flows in artificial open channels are non-uniform steady flows. The flow becomes non-uniform, one of which is because the flow passes through a channel whose geometry changes, including changes in width, height and slope angle of the channel. One of the structures in an artificial channel is a chute. Through this research, the effect of variations in chute slope on flow velocity and the type of flow that occurs downstream of the chute was studied. This research uses primary data with independent variables in the form of 4 variations in flow discharge or flow opening and 4 variations in slope. To analyze flow velocity, three measurement were used, using a current meter and float. Based on the analysis results, the greater the slope, the greater the flow velocity at the end of the chute and decreases further downstream. Flow velocity using a float produces a greater velocity because the float was on the surface of the flow, so it requires a correction number to become the average flow velocity. Because the influence of slope also had on velocity, the greater the slope, the greater the velocity, the more supercritical flow forms. Keyword: Open Channel Flow, Chute, Velocity, Non-uniform Flow, Slope Channel